Salt tolerance of sweet pepper seedlings - Slezák, K.; Terbe, I.; Kappel, N.; Tóth, K. (International Journal of Horticultural Science, 2002)
Laboratory germination tests have been made with three white fruit pepper varieties and with one spice pepper in filter paper rolls wetted with KCl solutions of different concentration. Parallel tests have been conducted with the other species (lettuce, tomato, kohlrabi) to compare the salt tolerance of paprika with that of other vegetable crops.In greenhouse, the action of KCl has been investigated with transplants raised in soil mixture, in rockwool and with seedlings transplanted from rockwool into soil mixture. Like the trials in the laboratory, the experiments in soil mixture have been made with other plant species, too.